STRUKTUR ANATOMIS VALVULA INTESTINALIS PARI GITAR (Rhinobatos typus) - Kusrini Kusrini; La Aba (UNIVERSITAS PGRI MADIUN, 2019)
Rhinobatos typus is included in Elasmobranchii Subclasses which has a unique intestine structure on internal part forms folds called valvula intestinalis as extension surface of food absorption. The uniqueness is influenced by habitat differences and food types. Ray’s habitat is in all waters, one of them is in waters Wakatobi Island. The aims of this research to determine Rhinobatos typus anatomical structure variations of valvula intestinalis were decided by observing intestine internal folds variations. Microanatomy structures were performed by making histological preparations using paraffin method, NBF (netral buffer formalin) solution fixation with Hematoxilin-Eosin (HE) staining. The result of the research indicated microanatomis structures of Rhinobatos typus has valvula intestinalis in spiral-shaped. Microanatomic structures of both internals valvula intestinalis from outside to inside consists of mucosa, submucosa, and muscularis.